Hubungan Self Care Management Dengan Quality Of Life Pada Pasien Diabetes Mellitus Tipe II Di Wilayah Kerja Puskesmas Batu X Kota Tanjungpinang - Erfina wardaniyanti; Linda Widiastuti; Utari Yunie Atrie (Journal of Innovative and Creativity, 2025)
Background: Type 2 Diabetes Mellitus (DM) prevalence reached 588.7 million adults globally in 2024, projected to rise to 852.5 million by 2050, with self-care management crucial for improving quality of life (QoL) amid rising complications.​ Objective: To analyze the relationship between self-care management and QoL among type 2 DM patients at Puskesmas Batu X, Tanjungpinang.​ Methods: This analytic cross-sectional study involved 77 patients selected via cluster and simple random sampling from a population of 768 registered cases. Instruments included Summary of Diabetes Self-Care Activities (SDSCA) and WHOQOL-BREF questionnaires. Data analysis used Spearman rank correlation (p<0.05) via SPSS 27.​ Results: Most respondents (58.4%) had good self-care management and high QoL (59.7%). Correlation coefficient was r=0.576 (p=0.000), indicating a strong positive relationship.​ Conclusion: Effective self-care management significantly enhances QoL in type 2 DM patients, supporting integrated primary care interventions.